Clustering of swamp land types against soil resistivity and grounding resistance - Dian Eka Putra; Muhammad Irfan Jambak; Zainuddin Nawawi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
In theory, the resistivity value of the soil is one of the factors that must be taken into account when planning a grounding installation. The resistivity value of swamp soil is 30 Ωm, as per the general requirements for electrical installation of 2011 (PUIL 2011). This value is identical to the resistivity of the soil type in The Institute of Electrical and Electronics Engineers (IEEE standard 80 in 2000), where the wet soil type has a resistivity value of 100 Ωm. It is difficult for electrical engineers to design construction on swamp land because the standard's representation of the features of swamp land does not accurately reflect the types of swamps or wetlands that exist in reality. The focus of this investigation is the resistivity value of swamp soil types. The results of this investigation will make a scientific contribution to the clustering of land at each soil resistivity value in freshwater, brackish water, saltwater, and acidic water swamp land. These soils have pH values that range from 3.5 to above 6. The research on swamp land clustering has revealed that each swamp has a distinctive resistivity value for the different types of swamp soil.